Improvement of Antioxidant Enzyme Level and Anti-Cadmium Activity in Cell-Lines Model as Effect of Thunbergia laurifolia Leaf Extract - Junsi , Marasri; Siripongvutikorn , Sunisa (New Horizons in Medicine and Medical Research Vol. 11, 2022)
Thunbergia laurifolia or Rang Jued has been used as an herbal tea and folk medicine as a detoxifying agent. Cd contamination is globally widespread and a serious public health problem. The endogenous antioxidant enzyme activities and malondialdehyde (MDA) production of the crude dried extract of T. laurifolia leaves, using cell models including murine macrophage (RAW264.7), human embryonic kidney (HEK293), and human hepatocellular carcinoma (HepG2) as a tested cell model were aimed to determine. In addition, the cytotoxicity including anti-cadmium (Cd) activity in all cells was measured. The experimental design was divided into 3 groups with combined, pre-, and post-treatments for investigating the anti-Cd toxicity, and cell viability was assayed with an MTT test (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide). The crude extract exhibited a low cytotoxicity and increased catalase (CAT) and glutathione peroxidase (GPx) activities by decreasing malondialdehyde (MDA) levels in HEK293 and HepG2 cells. In addition, the combination therapy effect was found when CaNa2EDTA, a chelating agent was tested. Therefore, it was concluded that the crude extract can protect against Cd-induced oxidative stress in cells. Furthermore, using the crude extract or drinking the herbal tea together with a chelating agent should have an efficacy advantage over using the individual crude extract or the chelating agent.